(untitled) (Bangladesh Journal of Medicine, 2026)
Background: Recent research has shown vitamin D deficiency as a risk factor for cognitive impairment. The study’s objective was to determine the association between vitamin D insufficiency and cognitive function in the elderly patient. Methods: This case control study was conducted in the department of neurology, Sir Salimullah Medical College, Mitford, Dhaka, Bangladesh from July 2022 to June 2023. Fifty cognitive impairment patients and 50 matched healthy control subjects were participated in the study. We evaluated subjects with cognitive function with available serum Vitamin D [2S (OH) D] levels. Descriptive statistics means and standard deviations and logistic regression analyses were performed by SPSS 25. Results: The mean age of patients was 70.7 +/-6.3 years and the control was 61.480 +/-7.15 years (p =0.613). Twenty-three subjects (46%) had severe cognitive impairment (SCI); 16 (32%) moderate cognitive impairment (MoCI); and 11 (22%) mild cognitive impairment (MCI). The overall prevalence of severe Vitamin D deficiency was 76%, being more frequent in the severe cognitive impairment group (47.4%), followed by the moderate cognitive (31.6%) and the MCI (21%) (p < 0.001) groups. Executive function was measured by the Clinical Dementia Rating (CDR) (6.2+/- 1.01, 3.8+/-1.0, 2.3+/-0.5; p = <0.10) respectively which were statistically significant. The same differences were noted between these groups in the Katz Index of independence in Activities in Daily Living (K Index) (4.0+/- 0.7, 2.6+/-0.5, 1.5+/-0.5; p = <0.10); verbal fluency (4.8 ± 1.3, 9.0 ± 2.3, 11.6+/-1.9 words, respectively; p < 0.01), and clock-drawing test scores (3.6 +/- 1.4, 6.2 ± 1.5 , 7.4 +/-1.4 points; p = <0.01) respectively. Cognitive status measured by MMSE was statistically significant with the sufficiency of Vitamin D group (11.8 ± 5.8 vs. 12.5 ± 4.7; p < 0.01).Executive function was measured by the Clinical Dementia Rating (CDR) was statistically significant with the sufficiency of Vitamin D group (4.6 ± 1.8 vs. 4.5 ± 2.1; p = 0.01) ; respectively, and statistically significant differences were observed when comparing with the cognitive impairment groups. In the univariate logistic regression analysis, the Vitamin D deficiency and insufficiency groups were significantly associated with MoCI (OR, 95% confidence interval [CI] 3.438 [1.256, 8.078]; p < 0.01 respectively, and OR, 95% CI 4.350 [1.258, 7.072]; p < 0.01, respectively). In the group with SCI, when compared with the sufficiency of Vitamin D control group, significant associations were also observed for the deficiency and insufficiency states (OR, 95% CI 5.953 [1.157, 15.792]; p < 0.01 and OR, 95% CI 5.125 [1.197, 15.434]; p = <0.01, respectively). Conclusion: Serum Vitamin D deficiency was associated with severe cognitive impairment; but not with the moderate cognitive impairment. So our study does not indicate that Vit D is a direct risk factor to cognitive decline, rather Vit D could be a covariable factor. Bangladesh J Medicine 2026; 37(1): 41-51